2023
DOI: 10.1093/nar/gkac1241
|View full text |Cite
|
Sign up to set email alerts
|

8-Oxoguanine targeted by 8-oxoguanine DNA glycosylase 1 (OGG1) is central to fibrogenic gene activation upon lung injury

Abstract: Reactive oxygen species (ROS) are implicated in epithelial cell-state transition and deposition of extracellular matrix upon airway injury. Of the many cellular targets of ROS, oxidative DNA modification is a major driving signal. However, the role of oxidative DNA damage in modulation profibrotic processes has not been fully delineated. Herein, we report that oxidative DNA base lesions, 8-oxoG, complexed with 8-oxoguanine DNA glycosylase 1 (OGG1) functions as a pioneer factor, contributing to transcriptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 70 publications
0
16
0
Order By: Relevance
“…Several recent studies suggested a role for OG as an epigenetic-like mark. Stress-induced accumulation of OG and recognition by OGG1 in promoter regions was shown to regulate gene expression of specific genes (8,9). In addition, apurinic (AP) sites generated by excision of OG activates gene transcription, which has been demonstrated for vascular endothelial growth factor ( VEGF ), endonuclease III-like protein 1 ( NTHL1 ) (10) and sirtuin 1 ( SIRT1 ) genes (11).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies suggested a role for OG as an epigenetic-like mark. Stress-induced accumulation of OG and recognition by OGG1 in promoter regions was shown to regulate gene expression of specific genes (8,9). In addition, apurinic (AP) sites generated by excision of OG activates gene transcription, which has been demonstrated for vascular endothelial growth factor ( VEGF ), endonuclease III-like protein 1 ( NTHL1 ) (10) and sirtuin 1 ( SIRT1 ) genes (11).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Pan et al. ( 57 ), small airway epithelial cells in culture could phenotypically convert to spindle-shaped mesenchymal cells, by a mechanism that involved OGG1-mediated molecular reprogramming in response to TGFβ exposure ( Figure 3 ). Cellular plasticity in EMT requires transcriptional networks mediated by key transcription factors, of particular importance is SMAD3 in the SMAD complex.…”
Section: Ogg1 Contributes To Inflammatory Tissue Remodelingmentioning
confidence: 97%
“…In the chromatin context, genome-wide binding of OGG1 is also mapped to illustrate stimulus-driven association of OGG1 with NFκB ( 56 ). Another study using chromatin immunoprecipitation (ChIP) assay shows that OGG1 reading 8-oxoGua accommodates phosphorylated SMADs complex binding to SMAD binding elements of pro-fibrotic genes, such α-SMA, fibronectin (FN) and collagen (COL), thereby facilitating gene activation ( 57 ). The physiological significance is striking, as OGG1 reading 8-oxoGua is temporally utilized to skew the repair function to trigger transcription, thereby repurposing OGG1 for the immune response.…”
Section: Ogg1 As An Epigenetic Reader and Erasermentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was shown that DNA-bound OGG1 at 8-oxoGua interacted with mitogen-and stress-activated kinase 1, which phosphorylates NFκB/RelA at serine 276, inducing expression of innate cytokines and chemokines [ 46 ]. A recent study documented that OGG1 at 8-oxoGua in the context of chromatin recruited phosphorylated SMAD2/3 complex and NFκB to their cognate binding sequence located in promoters of tissue remodeling genes including alpha-smooth muscle actin (α-SMA), collagen (COL), and fibronectin (FN) for excessive gene expression [ 41 , 47 ]. Another recent study revealed that Myc oncogene binding to the E-box promoter recognition sequence required OGG1 under oxidative stress conditions [ 48 ].…”
Section: Ogg1 Induces Dna Remodeling In Proximity Of Transacting Fact...mentioning
confidence: 99%